Karakteristik Tipologi Permukiman Kampung Jawa di Dusun Wanasari Denpasar, Bali - K. Rian Rahma Kusumawati; Widiastuti Widiastuti; Ni Ketut Agusintadewi (Universitas Islam Negeri Sunan Ampel Surabaya, 2022)
A slum settlement constitutes a residential environmental condition with a quality far below the occupancy worthiness standard. Slum neighborhoods are characterized by high building density, low environmental quality, poor infrastructure, and social problems that occur. One area in Denpasar City that belongs to slum settlement is Wanasari subvillage, Dauh Puri Kaja, North Denpasar. Kampung Jawa settlement area is divided into 9 RT (Neighborhood Associations). This area is not fully qualified for a slum, which can be divided into typologies of mild slum, moderate slum, and heavy slum levels. In general, each RT's physical conditions have various characteristics. This study was at least to analyze the characteristics of each typology group of slums. The research method used was mixed methods, in which the research stages were started by identifying the characteristics of the slum settlements in each RT area having been categorized according to the existing slum levels. The process of classifying these categories was carried out by observing and identifying slum settlements by looking at the physical aspects of the environment, the socio-economic conditions of the community, environmental facilities and infrastructure, and the environmental hazard conditions. The results of the study obtained indicate that the basic factors influencing the characteristics of Kampung Jawa settlement are the level of education, the type of occupation, the level of the economy, and the locations of the RT. The lower the factors that are owned, the lower the quality of the physical environment, infrastructure, and the level of hazard formed in the area of Kampung Jawa settlement. Keywords: slum settlement, characteristic identification, Kampung Jawa.